PENINGKATAN KEMAMPUAN MENULIS WACANA DESKRIPSI BERBASIS PEMBELAJARAN OUTDOOR CLASS SISWA KELAS X-4 SMA NEGERI 1 POLEWALI MANDAR - NFN Askarullah (Multilingual, 2013)
The aim of the research is to study the planning, operating, and evaluating the learning process  in the ability of writing descriptive text based on outdoor class of student of X-4 class, SMA Negeri 1 Polewali Mandar. This research is a class action research. The techniques of data collection are bservation and test. Analysis data techniques consist of four steps: 1) studying the data, 2) reducing,3) presentating data, and 4) concluding the research of result. The research result is applying outdoor activities study can develop the ability of student of X-4 class of Negeri1 Polewali Mandar. The study process in first cycle describes that the student have low interest in writing learning process, buton the second, they have been gradually had interest. It is showed by the increasing number of active students in learning process. The learning result shows that there is increasing number from first into second cycle. This can be described by the category: excellent, with the score interval of 86 – 100 infirst cycle, there is no student (0%) who gain the category, while there are 2 student (6,06%) who get excellent in the second cycle with accumulation score 86, or there is increasing in learning process for about 6,06% .The category of good, with score interval 71– 85 in the first cycle, there are 13students (39,40%) , while on the second there are 20 student (60,61%) or there is increasing in learning process for about 31,21%. On the category of fair, with the score interval 56–70, in the first cycle there are 16 siswa (48,49%) in this category, while on the second, there are 11 student (33,33%) . The category of poor with the score interval 41 – 55 and in the category of very poor withthe score interval of 1– 40 t there is no student (0%) on both categories. Based on the result, it can be concluded that the application of outdoor class activity can increase the writing ability of descriptivetext of the student of X-4 class of SMA Negeri 1 Polewali Mandar.